Development of Staphylococcus Enzybiotics: The Ph28 Gene of Staphylococcus epidermidis Phage PH15 Is a Two-Domain Endolysin - Magdy Mohamed Muharram; Ashraf Tawfik Abulhamd; Mohammed F. Aldawsari; Mohamed Hamed Alqarni; Nikolaos E. Labrou (MDPI AG, 2020)
Given the worldwide increase in antibiotic resistant bacteria, bacteriophage derived endolysins represent a very promising new alternative class of antibacterials in the fight against infectious diseases. Endolysins are able to degrade the prokaryotic cell wall, and therefore have potential to be exploited for biotechnological and medical purposes. Staphylococcus epidermidis is a Gram-positive multidrug-resistant (MDR) bacterium of human skin. It is a health concern as it is involved in nosocomial infections. Genome-based screening approach of the complete genome of Staphylococcus virus PH15 allowed the identification of an endolysin gene (Ph28; NCBI accession number: YP_950690). Bioinformatics analysis of the Ph28 protein predicted that it is a two-domain enzyme composed by a CHAP (22-112) and MurNAc-LAA (171-349) domain. Phylogenetic analysis and molecular modelling studies revealed the structural and evolutionary features of both domains. The MurNAc-LAA domain was cloned, and expressed in E. coli BL21 (DE3). In turbidity reduction assays, the recombinant enzyme can lyse more efficiently untreated S. epidermidis cells, compared to other Staphylococcus strains, suggesting enhanced specificity for S. epidermidis. These results suggest that the MurNAc-LAA domain from Ph28 endolysin may represent a promising new enzybiotic.